2014
DOI: 10.1111/cwe.12094
|View full text |Cite
|
Sign up to set email alerts
|

Housing Markets in China and Policy Implications: Comovement or Ripple Effect

Abstract: The overheated housing market has recently become a top priority of the Chinese authorities and whether the ripple effect exists is key to understanding this housing issue. The present paper uses a cointegration estimation technique for six first-tier Chinese cities during the 2003-2013 period to show that the comovements among housing prices in China are fully reflected in a long-run equilibrium. Using the Toda -Yamamoto causality test, the ripple effect is found to be characterized by a lead -lag relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 46 publications
2
23
1
Order By: Relevance
“…using quarterly housing price data from 2000 to 2012, they found that most of the provinces have bubbles and significant spillover effects exist among geographically adjacent regions. Another recent work by Chiang (2014) detected ripple effects among China's six first-tier cities from 2003 to 2013 by using the Toda-yamamoto (Ty) causality test. The results show that the ripple effect is characterized by a lead-lag relationship and Beijing is the main source of housing price appreciation, which should be targeted as the regulatory object.…”
Section: Literature Reviewmentioning
confidence: 99%
“…using quarterly housing price data from 2000 to 2012, they found that most of the provinces have bubbles and significant spillover effects exist among geographically adjacent regions. Another recent work by Chiang (2014) detected ripple effects among China's six first-tier cities from 2003 to 2013 by using the Toda-yamamoto (Ty) causality test. The results show that the ripple effect is characterized by a lead-lag relationship and Beijing is the main source of housing price appreciation, which should be targeted as the regulatory object.…”
Section: Literature Reviewmentioning
confidence: 99%
“…If the ripple effect is valid, there should be long-run relativities between the regions. As such, the government can identify the original shock of local housing prices and intervene with the real estate market in the source region, rather than that all regions (Chiang 2014). Therefore, the intervention policies could improve efficiency by using the right cure for the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, when spillovers from other cities are increasingly close to spillovers to other cities after 2014, this not only reveals the rise in total spillovers, but it also reflects the near-zero net spillovers across the six cities. This situation implies that spillover behaviour is a bilateral interaction among cities that have remarkable and equal spillovers ‘from’ and ‘to’ other cities – that is, there is co-movement among the six cities’ housing returns (Chiang, 2014). In fact, the co-movement among all urban housing markets fully indicates that very high system risk appears and the overheated housing market is now a national and not a local debate.…”
Section: Estimation Results and Policy Implicationsmentioning
confidence: 99%
“…Similarly, by dividing subsample periods in the presence of structural change, Brady (2014) showed that spillovers among states in the US have become stronger since the late-1990s. In the case of China, Chiang (2014) first applied the causality test to search for the source city of spillovers among six mega cities, finding the principal source city to be Beijing. Gong et al (2016) utilised the cointegration approach and causality with spatial correlations to indicate that there is little evidence of spillovers among these cities within the Pan-Pearl River Delta region.…”
Section: Literature Reviewmentioning
confidence: 99%